A Survey on Illicit Drug Use among University Students by Binary Randomized Response Technique: Crosswise Design - Nilgün Özgül (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This paper aims to introduce Randomized Response Techniques (RRT’s) and show that how RRT’s are implemented in surveys in which sensitive behaviors are investigated. For this purpose, the most popular designs of the Binary RRT are summarized and an experimental study is conducted on drug use among dormitory students at a public university in Ankara, Turkey. Despite the wide applicability of the drug use studies in Turkey, surprisingly any applications using indirect questioning techniques are not observed in the literature. In this study, for the first time, drug use behavior is investigated with Crosswise design which is the most frequently used indirect questioning technique and indirect questioning method (Crosswise design) is compared with direct questioning method to evaluate the effectiveness of the RRT. Results revealed that when Crosswise design is provided on asking sensitive questions, considerably minor response refusals are happened and significantly higher drug-use estimates are observed.